2012
DOI: 10.1590/s0103-90162012000600005
|View full text |Cite
|
Sign up to set email alerts
|

Technological, physicochemical and sensory characteristics of a Brazilian semi-hard goat cheese (coalho) with added probiotic lactic acid bacteria

Abstract: of lactic acid bacteria in the cheeses were greater than 10 7 cfu g -1 during storage. Cheeses with the added probiotic strains alone and in co-culture were better accepted than cheeses without the probiotic strains. It is suggested that goat "coalho" cheese could be a potential carrier of probiotic lactic acid bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
37
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 32 publications
10
37
0
5
Order By: Relevance
“…Previous studies reported similar counts for the same probiotic strains tested in this study during the refrigerated storage of goat dairy products (e.g., dairy beverages and cheese) Oliveira et al, 2012;Silveira et al, 2014), as well as for Lactobacillus spp. and Streptococcus thermophilus in bovine fresh white cheese (Yerlikaya & Ozer, 2014).…”
Section: Microbiological Analysis Of Ricotta Samples and Viability Ofsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies reported similar counts for the same probiotic strains tested in this study during the refrigerated storage of goat dairy products (e.g., dairy beverages and cheese) Oliveira et al, 2012;Silveira et al, 2014), as well as for Lactobacillus spp. and Streptococcus thermophilus in bovine fresh white cheese (Yerlikaya & Ozer, 2014).…”
Section: Microbiological Analysis Of Ricotta Samples and Viability Ofsupporting
confidence: 78%
“…After 7 days of storage, an increased (p ≤ 0.05) hardness was observed in all of the samples; however, the goat ricotta containing one of the tested probiotics had higher values (p ≤ 0.05) for this parameter compared with that of the ricotta lacking a probiotic (Table 3). The increase in hardness that occurred during storage can be attributed to the increased degree of crosslinking among the proteins resulting in the formation of threedimensional networks, which would be the consequence of the greater level of syneresis of these sample causing compression of the cheese structure and consequently placing the proteins in closer proximity (Lobato-Calleros et al, 2007;Oliveira et al, 2012). The difference (p ≤ 0.05) in the hardness of the goat ricotta samples containing a probiotic compared with that of the control samples could be related to changes in the cheeses promoted by bacterial metabolism.…”
Section: Instrumental Textural Profilementioning
confidence: 99%
“…1a and b). Ong et al (2007) and Oliveira et al (2012) reported a decrease in moisture content of probiotic cheeses of Coalho and Cheddar with prolonging storage time, respectively. A significant reduction in moisture content of probiotic Cheddar cheeses inoculated with Lactobacillus and Bifidobacterium bacteria strains and ripened at 8°C was also found (Ong and Shah 2009).…”
Section: Resultsmentioning
confidence: 99%
“…An increase in the storage time led to a decrease in the pH value (p < 0.05). Buriti et al (2005b) and Souza and Saad (2009) Oliveira et al (2012) for probiotic Coalho cheese supplemented with Lb. acidophilus also found similar trends in decreasing pH value during the storage.…”
Section: Resultsmentioning
confidence: 99%
“…To provide positive effects, probiotics must remain viable in the food products at a level of at least 10 6 cfu g -1 until the time of consumption [1]. Numerous strains of probiotic bacteria have been successfully added into different types of cheeses [2][3][4][5][6][7]. However, their viability until the time of consumption may be adversely affected by processing conditions as well as by the product environment and storage.…”
Section: Introductionmentioning
confidence: 99%